A school-based education concerning poisoning prevention in Isfahan, Iran - Kebriaee-zadeh, Javad (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: A school-based poisoning prevention program for young school children was implemented and evaluated in Isfahan city by Poison Control Center (PCC) of Food and Drug Deputy in 2010. OBJECTIVES: The aim of the program was to evaluate the effectiveness of education on children's knowledge on poisoning and its consequence and also on their attitude in case of exposure to poisonous or hazardous substances and poisoned patient. MATERIALS AND METHODS: In a pretest-posttest design, samples of 520 students from the fifth grade (10-11 years old), from twenty randomly selected girls’ and boys’ primary schools were involved in the study. These children were from two different geographical locations with different socio-economical levels (high-income and middle-income). After collection of pretest questionnaires, 6 poisoning education sessions were implemented in selected schools by trained teachers in a week. RESULTS: Following the education program, knowledge on various issues of poisoning significantly improved as did attitude to the poisonous agents and poisoned patients. In girl students, strong increase was found in knowledge on poisoning with carbon monoxide and heating devices from pretest to posttest. While in boy students, the strongest increase was in item of knowledge on poisoning prevention. Children living in the regions with middle-income conditions had more base-line knowledge and attitudinal aspect when compared with children with high-income condition. Comparison of all students showed significant differences (P < 0.001) on knowledge scores on various issues of poisoning before and after education. CONCLUSION: The school-based educational programs provide a good opportunity to poison information centers in preventing poisoning.